PENGARUH UKURAN PERUSAHAAN DAN FINANCIAL DISTRESS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marlisa Juniarsi; Ummi Kalsum; Fadhil Yamaly (Universitas Nusa Cendana, 2023)
This study aims to determine whether there is an effect of firm size and financial distress on firm value. This research includes this type of associative research. The research population is conventional banking companies listed on the Indonesia Stock Exchange for the 2017–2021 period, a total of 42 companies. The sample in this study was 12 companies with a total of 60 observational data points, using a purposive sampling technique. The data used in this research is secondary data. The analysis technique used is quantitative, with multiple linear regression analysis techniques. The partial test results show that there is a significant effect of firm size on firm value, and there is a significant effect of financial distress on firm value. Keywords: Company Value; Company Size; Financial Distress